Functional materials-enabled flexible electronic skin for flow field decoding - Hu, Xiaohe; Guo, Sheng; Chen, Yaqiong; Zhao, Fuqun (Frontiers in Electronics, 2025)
Flexible electronic skin has garnered significant interest due to its promising applications in underwater robotics, aircraft monitoring systems, and human healthcare systems. A critical requirement for flexible electronic skin is to exhibit high sensitivity, stretchability, and stability. Functional materials, as essential components of flexible electronic skin, significantly influence the overall performance of the device. Consequently, a variety of material and structural designs have been developed to enhance the performance of functional materials. This perspective delves into recent advances in the development of functional materials and engineering strategies that endow electronic skin with sensitivity, stretchability, and stability. The applications of the smart electronic skin for precise decoding of flow field are highlighted. Finally, a forward-looking perspective is provided on the future of flexible electronic skin for flow field decoding, which outlines the challenges and opportunities for ongoing research and innovation in this field.